Validity and reliability of a new test of planned agility in elite taekwondo athletes - Chaabene, H.; Negra, Y.; Capranica, L.; Bouguezzi, R.; Hachana, Y.; Rouahi, M. A.; Mkaouer, B. (The Journal of Strength and Conditioning Research, 2018)
This study aimed to examine the validity, reliability, and sensitivity of a new test of planned agility in elite taekwondo athletes and to establish its relationship with sprint-time, jumping ability, and dynamic balance. Twenty-seven (20 males and 7 females) taekwondo athletes participated in this study. They performed taekwondo-specific agility test (TSAT) in 2 occasions (i.e., test-retest). In addition, they performed jumping ability (i.e., squat jump, countermovement jump, standing long jump, and 3-hop jump), sprint-time (5- and 20-m dash), and dynamic balance (i.e., Y-test) tests along with a planned agility test (i.e., T-test). To establish TSAT's construct validity, 2 subgroups were identified based on their international and national taekwondo results: top elite (9 males and 2 females) and elite (11 males and 2 females). Taekwondo-specific agility test showed high relative and absolute reliability as well as a good ability to detect small and meaningful performance change. Top-elite athletes showed greater (p < 0.001) TSAT performances (4.5 ± 0.4 seconds) compared with their elite (5.3 ± 0.4 seconds) counterparts. Receiving operating characteristic (ROC) analysis showed that TSAT was able to discriminate athletes of different competitive level as revealed by an area under the ROC curve of 0.94 (95% confidence interval: 0.76-0.99). Taekwondo-specific agility test demonstrated significant association with the T-test (r = 0.71; shared variance = 50%), which is considered as a gold-standard planned agility test. In addition, results showed moderate-to-large associations between TSAT and jumping ability, sprint-time, and dynamic balance tests. The TSAT might be considered as a valid and reliable test to evaluate specific agility of taekwondo athletes.